Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: relevant categories of their functioning from the research perspective, a scoping review. Issue 2 (17th February 2021) - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Graessel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann
Abstract : Objectives: The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design: A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting: Home, primary care. Participants: Community-dwelling adults aged 75 years and above. Results: From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the 'activities and participation' component. The most frequently identified categories were ' memory functions', 'dressing' and 'changing basic body position'. Conclusions: This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients. Trial registration numbers: PROSPERO (CRD42017067784), Versorgungsforschung Deutschland Datenbank (VfD_17_003833) and ClinicalTrials.gov (NCT03384732 ).